Assessment of the ecological and ameliorative condition of the soil and potential risks when using different types of irrigation of decorative plants - O. O. Gololobova; N. V. Maksymenko; V. L. Bezsonnyi (Людина і довкілля: Проблеми неоекології)
Purpose. Assessment of the ecological and reclamation state of the soil and the probable risks when using different types of irrigation: traditional sprinkling and subsurface drip irrigation.